1961
DOI: 10.1002/app.1961.070051306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of emulsion polymerization of vinylidene chloride. III. Effects of stirring rate on kinetics

Abstract: The effect of stirring speed on the rate of the persulfate‐catalyzed polymerization of vinylidene chloride has been determined. It was found that the first‐stage rate decreases with increasing stirring speed, that the second‐stage rate increases with increasing stirring speed, and that the rate of the third stage is independent of stirring speed. These results, as well as those of an earlier paper, may be explained in the following manner. The second stage slow‐down results from monomer starvation, caused by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…At a low stirring speed, the rate of monomer transport (R a ) to polymerising particles is diffusion controlled (Evans et al, 1961;Nomura et al, 1972). This has been associated with a * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…At a low stirring speed, the rate of monomer transport (R a ) to polymerising particles is diffusion controlled (Evans et al, 1961;Nomura et al, 1972). This has been associated with a * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…Early literature indicates a significant influence of the degree of agitation on the behaviour of emulsion polymerisations. [2] In practice, there has been found a ''safe bound'' within which the rate of polymerisation (R p ) and number of particles (N p ) are independent of the stirring speed. [3] At a high stirring speed, particles may coagulate to give a smaller N p as well as a lower R p .…”
Section: Introductionmentioning
confidence: 99%
“…[3] At a low stirring speed, the rate of polymerisation is diffusion controlled. [2][3][4][5] This has been associated with a formation of a larger number of particles. [6][7][8] The effects of impeller speed and/or type on the rate of copolymerisation, molecular weights, [4,9] and particle size distribution [10] have been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because polymerization is highly exothermic, an efficient agitation is required to ensure a uniform temperature throughout the reactor and to maximize the heat-removal rate. For vinylidene chloride, Evans et al 5 observed different effects of the agitation for the three stages in which emulsion polymerization can be divided. 2,3 Most of the works reported in the literature on the effect of agitation on emulsion polymerization focused on batch reactors.…”
Section: Introductionmentioning
confidence: 99%